2013
DOI: 10.5194/bg-10-2973-2013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of dust deposition on phytoplankton ecophysiology and succession in a low-nutrient low-chlorophyll ecosystem: a mesocosm experiment in the Mediterranean Sea

Abstract: In this study, we investigate the response of the phytoplankton community, with emphasis on ecophysiology and succession, after two experimental additions of Saharan dust in the surface water layer of a low-nutrient low-chlorophyll ecosystem in the Mediterranean Sea. Three mesocosms were amended with evapocondensed dust to simulate realistic Saharan dust events, while three additional mesocosms were kept unamended and served as controls. The experiment consisted in two consecutive dust additions and samples we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 91 publications
8
48
2
Order By: Relevance
“…As with the POC dust fluxes and optical parameters, the phytoplankton community responded dif- ferently to both seedings with a distinct magnitude, timing, and composition change (Giovagnetti et al, 2013). Although optical measurements revealed rapid particulate export following the first seeding (Bressac et al, 2012), c p (0-10 m) continually increased during the T 0 -T 53 period (Fig.…”
Section: The Dynamics and Timing Of Particulate Exportmentioning
confidence: 86%
See 3 more Smart Citations
“…As with the POC dust fluxes and optical parameters, the phytoplankton community responded dif- ferently to both seedings with a distinct magnitude, timing, and composition change (Giovagnetti et al, 2013). Although optical measurements revealed rapid particulate export following the first seeding (Bressac et al, 2012), c p (0-10 m) continually increased during the T 0 -T 53 period (Fig.…”
Section: The Dynamics and Timing Of Particulate Exportmentioning
confidence: 86%
“…Furthermore, following both seedings, the biomass of siliceous phytoplankton remained very low and a major response was observed for non-siliceous phytoplanktonic organisms (Giovagnetti et al, 2013). Although calcified organisms likely responded to the seedings, the fraction of biogenic CaCO 3 collected in sediment traps of + dust mesocosms remained negligible (3 ± 0.5 % in mass; .…”
Section: A Comparison Between Primary Production Poc and Lithogenicmentioning
confidence: 97%
See 2 more Smart Citations
“…When a second dust wet deposition was simulated, iron dissolution from the dust particles was then evidenced due to the excess Fe binding ligand concentrations produced by the enhanced biological activity (Wuttig et al 2013). When simulating dust wet deposition at least a doubling of Chla (mainly attributed to small phytoplankton (<3 μm); Giovagnetti et al 2013) was observed but the Chla concentrations remained very low (maximum values 0.22 μg L-1) maintaining the oligotrophic status of the tested waters . Laghdass et al (2011) investigated the effect of dust deposition on the diversity of the heterotrophic bacterial community.…”
Section: Experimental: In Situ Mesocosmsmentioning
confidence: 99%